A Refraction Experiment Using Ocean Bottom Semismographs and Implications of a Structural Model of the Crest of the Mid-Atlantic Ridge at 37 deg N - Rowlett,Hugh; McCamy,Keith; Fox,Paul J (1978)
A main goal of marine seismology is to measure seismic velocities to contrain petrologic and structural models of the ocean crust. This is especially important for models of the lower crust which has not yet been reached by drilling and cannot be directly examined. This paper describes the results of a refraction experiment that investigates the discrepancies of previous work in the crestal mountains at 37 N. We also compare the results of our refraction experiment with the other refraction experiments conducted in the median valley at 37 N and propose a structural model for the upper 3 km of oceanic crust at 37 N based on the better constrained experiments. Prepared in cooperation with State Univ. of New York at Albany. Dept. of Geological Sciences.